Intelligent Information and Database Systems Third International Conference, ACIIDS 2011, Daegu, Korea, April 20-22, 2011, Proceedings, Part II - Nguyen, Ngoc Thanh; Kim, Chong-Gun.; Janiak, Adam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNAI 6591 and LNCS 6592 constitutes the refereed proceedings of the Third International Conference on Intelligent Information and Database Systems, ACIIDS 2011, held in Daegu, Korea, in April 2011. The 110 revised papers presented together with 2 keynote speeches were carefully reviewed and selected from 310 submissions. The papers are thematically divided into two volumes; they cover the following topics: intelligent database systems, data warehouses and data mining, natural language processing and computational linguistics, semantic Web, social networks and recommendation systems, technologies for intelligent information systems, collaborative systems and applications, e-business and e-commerce systems, e-learning systems, information modeling and requirements engineering, information retrieval systems, intelligent agents and multi-agent systems, intelligent information systems, intelligent internet systems, intelligent optimization techniques, object-relational DBMS, ontologies and knowledge sharing, semi-structured and XML database systems, unified modeling language and unified processes, Web services and semantic Web, computer networks and communication systems.
Keywords: Computer science; Computer software; Database management; Data mining; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Information Systems Applications (incl.Internet).; Database Management; User Interfaces and Human Computer Interaction; Algorithm Analysis and Problem Complexity